Neotropical spittlebugs related to Neaenini (Hemiptera, Cercopidae) and the origins of subfamily Cercopinae - Hamilton, K.g. Andrew (Zootaxa, 2016)
The Central American tribe Neaenini, originally comprising only the monobasic genus Neaenus Fowler, was thought to be transitional between Cercopinae and Aphrophorinae. The genus is here enlarged by 5 (1 unnamed)  additional species including 2 in a distinctive new subgenus Neaniskus. Keys are presented to 5 species of Neaenus, to 12 allied Neotropical genera and their 57 species: 12 of Tomaspisinella Lallemand, 1927 (=Hemitomaspis Lallemand, 1949, syn.nov. and 3 distinctive new subgenera Meretricula, Merinx and Merulatomus), 14 species of Microsargane Fowler, 1897 (=Ecothera Melichar, 1915, syn.nov., with 2 distinctive new subgenera Microrhaphe and Microtholia) and 31 species of Zuata Fennah, together with 2 species of Helioptera gen. nov. and 6 monobasic genera (Liparonotum gen. nov., Marcion Fennah, Menytes gen. nov., Microclimax gen. nov., Microlaqueus gen. nov. and Simorhina Jacobi). The small Neotropical genera Tomaspisina Distant and Olcotomaspis Lallemand (with 2 new combinations and subgenus Hyalotomaspis Lallemand, stat.nov.) appear to be allied to the large old-world genus Phymatostetha Stål rather than to any new-world Cercopinae. A check list is presented to these 13 genera and their 76 species (of which 30 are new to science and 5 of Zuata are new synonyms). Males are described for 5 species previously known from females but males of 9 (in 6 genera) are still unknown. Male genitalia define a new tribe of Cercopinae, Microsarganini (Microsargane was formerly placed in Aphrophorinae) that also includes Liparonotum, Microclimax and Microlaqueus. Almost half of the genera are monobasic without synapomorphies to Aphrophorinae, suggesting that these genera (including several genera resembling both Aphrophorinae and Cercopinae) represent relict lineages at the base of the subfamily Cercopinae.